Awareness of care and importance of primary teeth among mothers in Yasuj 2017 - Zahra Hashemi; Leila Manzuri; Fatemeh Rahimi; Maryam Farzadmoghadam; Seyed Ali Saleh Gholami (Babol University of Medical Sciences, 2019)
Introduction: Healthy primary teeth are necessary for a child's physical and mental health. Increasing mothers' awareness of the importance of these teeth is significant for the creation of healthy teeth in their children's mouths. Thus, the aim of this study was to evaluate mothers' awareness of the importance and care of their children's primary teeth in Yasuj Material & Methods: In this cross-sectional study, 384 mothers with their children aged ≤6 years were enrolled. The data were collected via a 12-item researcher-made questionnaire and analyzed using mean, standard deviation, Spearman and binary logistic regression tests. Results: The mean age of mothers was 29.71±5.04 years. The mean score of mothers' awareness of the importance of primary teeth was 5.9±2.76 ) score of  0-12).No mothers had good awareness, 119 (31%) and 265 (69%) mothers had moderate and poor awareness in this regard, respectively. A significant relationship was found between mothers' age and awareness (p=0.0001, r=0.18) as well as between parental education level and awareness (p=0.0001, r=0.25). Parental education levels including subdiploma P=0.009, EXP (B)=15.19, 0.95% CI= 1.97-116.91; diploma and technician P=0.0001, EXP (B)=39.42, 0.95% CI= 5.03-308.81; Bachelor's degree P=0.001, EXP (B)=27.02, 0.95% CI= 3.55-205.73; Master's degree and higher P=0.003, EXP (B)=26.26, 0.95% CI= 2.95-233.26 as well as maternal age P=0.008, EXP (B)=1.07, 0.95% CI= 1.02-1.14  were predicting factors for mothers' awareness of the importance and care of the primary teeth. Conclusion: Considering the undesirable level of mothers' awareness of the importance and health, the interventions  and planning are essential to enhance mothers' awareness in this regard.